2009
DOI: 10.1007/s00408-009-9208-9
|View full text |Cite
|
Sign up to set email alerts
|

Cheyne-Stokes Respiration and Prognosis in Modern-Treated Congestive Heart Failure

Abstract: In patients with congestive heart failure (CHF), a high prevalence of sleep-disordered breathing has been described. Cheyne-Stokes respiration (CSR) is present in up to 40% of patients with CHF. During the last decade, the medical treatment has been substantially improved. This study was designed to analyze the prognosis of CSR in modern-treated patients with CHF. For this purposes, in 57 patients with CHF who received modern treatment, a 5-year follow-up after initial full night polysomnography was performed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…13e26 Eight earlier studies 13,16,17,19,20,23,25,26 reported a higher mortality in patients with CSA, although 6 others failed to demonstrate an increased mortality in patients with CSA. 14,15,18,21,22,24 Most of those studies had $1 of the following limitations: small patient populations with few end points during follow-up, retrospective study design, use of polygraphy rather than polysomnography as criterion standard to detect CSA, no uniform use of ventilation, and lack of multivariate analysis to adjust for confounding variables. The 1st small study designed to specifically determine the impact of CSA on mortality in HF was reported by Hanly et al in 1996.…”
Section: Csa and Transplant-free Survivalmentioning
confidence: 99%
“…13e26 Eight earlier studies 13,16,17,19,20,23,25,26 reported a higher mortality in patients with CSA, although 6 others failed to demonstrate an increased mortality in patients with CSA. 14,15,18,21,22,24 Most of those studies had $1 of the following limitations: small patient populations with few end points during follow-up, retrospective study design, use of polygraphy rather than polysomnography as criterion standard to detect CSA, no uniform use of ventilation, and lack of multivariate analysis to adjust for confounding variables. The 1st small study designed to specifically determine the impact of CSA on mortality in HF was reported by Hanly et al in 1996.…”
Section: Csa and Transplant-free Survivalmentioning
confidence: 99%
“…Cardiac resynchronization therapy has also been shown to improve sleep quality, QoL as well as cardiac pump function and patients’ outcome. Therefore, this albeit very expensive therapy should be evaluated in patients with severe heart failure associated with ventricular asynchrony due to conduction abnormalities [69]. If cardiac therapy fails to reverse CSR, directly influencing the respiratory controller to smooth periodic breathing arises as the goal of therapy [9,10,70].…”
Section: Treatment Of Csrmentioning
confidence: 99%
“…; Hagenah et al . ). In experimental HF, we found that disordered breathing patterns under normoxia were markedly reduced after ablation of RVLM‐C1 neurones (Figs and , and Table ).…”
Section: Discussionmentioning
confidence: 97%